Two Lensed Star Candidates at z ≃ 4.8 behind the Galaxy Cluster MACS J0647.7+7015 - Ashish Kumar Meena; Adi Zitrin; Yolanda Jiménez-Teja; Erik Zackrisson; Wenlei Chen; Dan Coe; Jose M. Diego; Paola Dimauro; Lukas J. Furtak; Patrick L. Kelly; Masamune Oguri; Brian Welch; et al. (The Astrophysical Journal Letters, 2023)
We report the discovery of two extremely magnified lensed star candidates behind the galaxy cluster MACS J0647.7+015 using recent multiband James Webb Space Telescope (JWST) NIRCam observations. The star candidates are seen in a previously known, z _phot ≃ 4.8 dropout giant arc that straddles the critical curve. The candidates lie near the expected critical curve position, but lack clear counter-images on the other side of it, suggesting these are possibly stars undergoing caustic crossings. We present revised lensing models for the cluster, including multiply imaged galaxies newly identified in the JWST data, and use them to estimate background macro-magnifications of at least ≳90 and ≳50 at the positions of the two candidates, respectively. With these values, we expect effective, caustic-crossing magnifications of ∼[10 ^3 –10 ^5 ] for the two star candidates. The spectral energy distributions of the two candidates match well the spectra of B-type stars with best-fit surface temperatures of ∼10,000 K, and ∼12,000 K, respectively, and we show that such stars with masses ≳20 M _⊙ and ≳50 M _⊙ , respectively, can become sufficiently magnified to be observable. We briefly discuss other alternative explanations and conclude that these objects are likely lensed stars, but also acknowledge that the less-magnified candidate may alternatively reside in a star cluster. These star candidates constitute the second highest-redshift examples to date after Earendel at z _phot ≃ 6.2, establishing further the potential of studying extremely magnified stars at high redshifts with JWST. Planned future observations, including with NIRSpec, will enable a more detailed view of these candidates in the near future.